Effects of ocean acidification on benthic organisms in the Mediterranean Sea under realistic climatic scenarios: A meta-analysis - ZUNINO, SERENA; Melaku Canu, Donata; Bandelj, Vinko; Solidoro, Cosimo (Regional Studies in Marine Science, 2017)
Ocean acidification is expected to cause significant changes in the marine environment over the coming century. The effects of acidificationonorganisms’ physiology have been studied over the pasttwodecades. However, the experimental findings are not always easily comparable because of differences in experi- mental design, and comparable experimentsdonot always produce similar results. To rigorously integrate the current knowledge, we performed a meta-analysis of published studies focused on benthic organisms in the Mediterranean Sea, both in controlled manipulative experiments and in situ experiments near vent areas. In each experiment, the effect of acidification was calculated as the log-transformed response ratio (LnRR) of experimental versus control conditions. The quantitative results obtained by the meta-analysis highlight: (a) an increase in fleshy algae cover, which may lead to a competitive advantage over calcify- ing macroalgae; (b) a reduction of calcification by both algae and corals; (c) an increase in seagrass shoot density under low pH; and (d) a general increase in the photosynthetic activity of macrophytes.